A citation analysis of corporate social responsibility (1970-2014): insights from Islamic perspective. Issue 3 (11th September 2018) - Alfakhri, Yazeed; Nurunnabi, Mohammad; Alfakhri, Demah
Abstract : Purpose: The purpose of this paper is to analyse the citations of scientific research on the concept of corporate social responsibility (CSR) from 1970 to 2014. In particular, several interconnected research questions were investigated: How did the conceptualisation of CSR change from 1970 to 2014? What is the general direction of the change? How does Islamic CSR emerge? Design/methodology/approach: An in-depth analysis was performed with the use of the data analysis tool available in the Web of Science. The study categorises CSR into four areas: business ethics and corporate governance; management; marketing; and others. The first three categories were based on the Chartered Association of Business Schools' Academic Journal Guide 2010 and 2015 (UK). Findings: The findings reveal that 67.19 per cent articles have been published based on the ranked journals of Academic Journal Guide 2010 and 2015. The findings of the study will help to inform future areas of CSR. The top journals which published most articles from Academic Journal Guide 2015 are Journal of Business Ethics and Corporate Social Responsibility and Environmental Management . Practical implications: The findings suggest that the remit of sustainability from Islamic perspective is wider. Islamic marketing, as an area, remains largely in need of empirical research. The business communities should successfully integrate Muslim communities into their marketing strategies. Originality/value: To the best of the knowledge, this is the first study to explore citation analysis of general CSR literature and Islamic CSR. The study finds that there has been an increase in interest in this subject of CSR and Islam in the recent years. Future research is needed on theory and methodological analysis of general CSR field and Islamic CSR field.